A rare case report of Poland syndrome in neonates - Prashant Kumar; Manvi Bhatia; C M Sharma (International Journal of Medical Research and Review, 2015)
The Poland's anomaly was first described in 1841 by Sir Alfred Poland as a syndrome presenting with absence or underdevelopment of pectoralis major muscle, associated in some cases with a hypoplasia of the breast, an agenesis of 2, 3, 4 and 5 ipsilateral costal cartilages, and an ipsilateral webbing of the fingers (cutaneous syndactyly). Other associated abnormalities may include dextrocardia, diaphragmatic hernia and renal anomalies etc. Poland syndrome most often affects the right side of the body, and occurs more often in males than in females. It is usually considered a unilateral condition but rarely, bilateral.